BACKGROUND MAHASISWA, SMART CITY CONCEPT DIMODERASI DENGAN TRANSPARANSI ANGGARAN PEMERINTAH DKI JAKARTA - Hurian Kamela; Darlin Aulia (Jurnal Riset Terapan Akuntansi, 2025)
This study examines how students’ backgrounds influence their understanding of the Smart City concept, particularly in relation to budgeting. In the digital era, Smart City initiatives are increasingly important for enhancing public service efficiency. However, students’ comprehension may vary depending on their educational background, academic discipline, and access to information on government policies. Using a quantitative survey method, data were collected through questionnaires distributed to students from various disciplines in DKI Jakarta. The data were analysed using moderation regression techniques. The results indicate that students’ backgrounds significantly affect their understanding of Smart City; those from technology and public policy fields demonstrate better comprehension than those from other disciplines. Furthermore, budget transparency is identified as a moderating variable that strengthens this relationship. Students with greater access to budget information show higher awareness of how Smart City concepts can be applied. These findings underscore the vital role of budget transparency in enhancing students’ understanding of Smart City initiatives and promoting their active participation in developing more intelligent and sustainable cities. Keywords: Smart City, background, transparency, DKI Jakarta.